Fibrinolytics in the Treatment of Complicated Pleural Effusions - Coelho, Ana (2016)
Introduction: The treatment of complicated pleural parapneumonic effusions with intrapleural instillation of fibrinolytics, has shown similar results as surgical treatment. The present study aimed to evaluate the results of the use of intrapleural instillation of fibrinolytics in the treatment of complicated pleural parapneumonic effusions, in patients followed in our hospital.Material and Methods: A retrospective review of all the patients (aged between one month and 18 years) diagnosed with complicated parapneumonic effusions, which had chest drain insertion with intrapleural instillation of fibrinolytic, between January 2005 andDecember 2013, was undertaken.Results: A total of 37 patients were identified. Mean duration of hospital stay was 17 ± 7.60 days. Chest drain was placed in the first 48 h of hospital admission in most of the patients (89.2%), with a mean of six days of drainage. Treatment failure was reported in 2.7% of cases and was related with effusion recurrence. This patient underwent video-assisted thoracoscopic surgery with the need to convert to open thoracotomy. A favorable outcome was achieved in 96.9 % of cases.Discussion: In our review, therapeutic success rate was as expected, with a failure rate below those reported in literature. We present intrapleural instillation of fibrinolytics and video-assisted thoracoscopic surgery as part of the same protocol, in which fibrinolytic therapy is the first-line treatment.Conclusion: The therapeutic option presented shows a low failure rate and avoids a more aggressive surgical procedure. We consider this an effective treatment option, with low sequelae rate.